Social policy research in the UK, with special reference to crossnational comparative research: ZeS country report - Peter Taylor-Gooby (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2012)
The Country Reports on the State of Social Policy Research are published from time to time in the Working Paper Series of the Center for Social Policy. An experienced scientist offers an overview of the central institutions and persons in comparative and national social policy research in his or her country. These reports can never depict the whole landscape but they can help by focusing our attention on the strengths, the special expertise, and the special features of the respective research community as it confronts welfare state challenges and reforms in the 21st century. Each country report may provide its readers with a starting point for their own research, and it can point to the well-travelled networks and to the dominant issues at hand. – – Die Länder-Reporte Sozialpolitikforschung erscheinen in unregelmäßigen Abständen in der Arbeitspapierreihe des Zentrums für Sozialpolitik. Vom Standpunkt einer erfahrenen Wissenschaftlerin oder eines erfahrenen Wissenschaftlers wird hier eine Übersicht über die relevanten Institutionen und Personen der vergleichenden und nationalen Sozialpolitikforschung in dem jeweiligen Land gegeben. Diese Berichte können keinen Anspruch auf Vollständigkeit der Darstellung erheben. Sie sollen aber die Stärken, Expertisen und Besonderheiten der jeweiligen Forschungslandschaft hervorheben, die jede auf ihre Weise die Herausforderungen und Reformen der Wohlfahrtspolitiken im 21. Jahrhundert konfrontiert. Sie können den Leserinnen und Lesern Ansatzpunkte für die eigene Forschung und Forschungszugänge bieten, die bestimmenden Forschungsthemen kennzeichnen und die Netzwerkbildung fördern.
Keywords: 300